Enhancing Scattering Strength Improvement and Color Uniformity in White Light-Emitting Diodes Using High Concentration of Yttrium Oxide - Cong, Pham Hong; Loan, Nguyen Thi Phuong; Tung, Ha Thanh (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
This study investigates the effect of yttrium oxide (Y2O3) doping on the phase evolution of barium titanate (BaTiO3), a key dielectric material used in multilayer ceramic capacitors (MSCCs). Two types of starting powders were examined: pure BaTiO3 and a commercial X7R composition containing 1 wt% Y2O3. Using the solid-state method under high temperature, Y2O3 was added in varying amounts, and the powders were processed under controlled sintering conditions to evaluate its influence on phase formation. The resulting ceramics were characterized to determine formational alterations as well as the potential generation of secondary phases. Increasing Y2O3 content led to a transmutation from the tetragon structure to a merger between tetragon as well as cubic phases. The commercial X7R powder exhibited greater densificating process, surpassing pure BaTiO3 and formed a cuboid formation under greater Y2O3 concentrations. Notably, the sample doped with 20 wt% Y2O3 produced the Ba6Ti17O40 phase, augmenting scattering capacity and color uniformity. These findings clarify the role of Y2O3 in phase evolution and highlight its implications for optimizing BaTiO3-based MSCC materials.